Status, distribution and habitat use by Mugger crocodile (Crocodylus palustris) in and around Koshi Tappu Wildlife Reserve, Nepal. Issue 8 (August 2022) - Bhattarai, Divya; Lamichhane, Saurav; Pandeya, Pratik; Bhattarai, Santosh; Gautam, Jeetendra; Kandel, Ram Chandra; Pokheral, Chiranjibi Prasad
Abstract: Mugger crocodile is found in various locations of Nepal, ranging from Eastern to Western lowlands, and is also a resident crocodilian of the Koshi Tappu Wildlife Reserve (KTWR). Fewer studies have been carried out on the status and distribution of this crocodilian with limited information on its habitat characteristics. This study sets forth to highlight the population status, distribution and habitat use by mugger crocodile in and around KTWR. Detailed surveys were conducted in the rivers, natural and private ponds of the KTWR in December 2020. Every 500 m along the survey transects, habitat characteristics were recorded in each habitat station as part of the habitat survey. The dependent variables were presence or absence of mugger crocodile in each habitat station. Meanwhile, the independent variables included habitat predictors such as; water depth, slope, elevation, distance to roads, distance to settlements, bank substrate, and human disturbance. Generalized Linear Model under binary logistic regression was employed to test variables associated with presence and absence of muggers for statistical significance. The population survey of the muggers was assessed by day counts either using dugout canoe or walking along transects. During the research period, 35 individuals of muggers were recorded. The probability of mugger sighting augmented with increased slope and depth. 34 muggers (97.14 %) were basking, while 1 (2.85%) were seen swimming out of the total muggers detected. In private and public ponds, 22 muggers were sighted, while 13 were sighted in the main Koshi river, its branches, and the Moriya river. Sixteen muggers (45.71 %) were sighted within the reserve, while the remaining 19 muggers (54.28 %) were sighted in the buffer-zone areas. The probability of mugger sighting varied considerably with regard to slope and water depth among the seven habitat predictors examined. In lieu of prevailing fishing pressure in the river systems of the KTWR and easy availability of prey species for muggers in private fishponds; the muggers are likely use private fishponds more frequently. In order to subdue the muggers inside the KTWR, the reserve authority has a vital role for proper habitat management decisions and regulation of fishing activities. Abstract : Habitat survey; Transects; Variables; Generalized linear model; Binary logistic regression.